Comparative Study on the Effect of Various Implant-Abutment Connections on Microbial Leakage - Aditya Acharya; Richa Sahai; K. Anusha Ravindra; Shivani Mishra; Guruprasad Uikey; Mustansir M. Electricwala (Journal of Pharmacy and Bioallied Sciences)
Background: Microbial leakage at the implant-abutment interface can lead to peri-implantitis, jeopardizing the long-term success of dental implants. The design and type of implant-abutment connection play a significant role in minimizing this leakage. Materials and Methods: Thirty dental implants were divided into three groups (n = 10): group I – internal hex connection, group II – external hex connection, and group III – Morse taper connection. Each implant was inoculated with Escherichia coli bacteria and assembled under standardized torque. The assemblies were incubated for 7 days at 37°C. Microbial leakage was assessed by culturing samples from the external surfaces of each implant system on MacConkey agar. The bacterial growth was quantified by colony-forming units (CFU) analysis. Results: The microbial leakage was significantly different among the three groups (P < 0.05). Group II (external hex) exhibited the highest microbial leakage with an average CFU of 1.25 × 106 followed by group I (internal hex) with 6.5 × 105 CFU. Group III (Morse taper) demonstrated the least microbial leakage, with an average CFU of 1.8 × 104 The Morse taper connection showed superior sealing ability compared to the other two connections. Conclusion: The type of implant-abutment connection significantly affects microbial leakage. Morse taper connections exhibit the least leakage and may be preferred to improve the long-term success of dental implants. Further clinical studies are required to corroborate these findings.